2008
DOI: 10.1260/026361708786035413
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of the Natural Carbon–Mineral Sorbent Shungite

Abstract: Physicochemical methods were used for a comprehensive study of the structural/sorption properties of the natural mineral shungite. It was shown that the composite structure of the mineral determines its main physicochemical characteristics. The isosteric heat of adsorption of water vapour was estimated by calorimetric methods as 70 kJ/mol. This value corresponds to the interaction of water molecules with the vicinal hydroxy groups of the silica constituent of shungite; adsorption heats with values in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A number of systems were examined to check the proposed method for calculating the H3 hysteresis loop in the low pressure region: the adsorption of water at T = 298 K on a lunar soil sample [2], adsorption of water at T = 293 K on shungite [4] and kaolinite [3,7], and the adsorption of pyridine at T = 323 K on montmorillonite [5,6]. The corresponding adsorption-desorption isotherms are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of systems were examined to check the proposed method for calculating the H3 hysteresis loop in the low pressure region: the adsorption of water at T = 298 K on a lunar soil sample [2], adsorption of water at T = 293 K on shungite [4] and kaolinite [3,7], and the adsorption of pyridine at T = 323 K on montmorillonite [5,6]. The corresponding adsorption-desorption isotherms are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the commonly accepted theory of adsorption hysteresis, the abscissa of the extreme left-hand point of the hysteresis loop corresponds to relative pressure of the adsorbate in the bulk phase not less than p/p s » 0.4-0.5 [1]. On the other hand, considerable experimental work has shown that the H3 hysteresis loop continues into the low pressure region and often does not close even as p/p s ® 0 [2][3][4][5][6][7][8]. In 1957, Arnell and McDermot [9] proposed that hysteresis at low pressures should be attributed to the formation of traps in the adsorbent upon adsorption.…”
mentioning
confidence: 99%
“…Adsorbents such as lunar regolith, shungite, and kaolinite are characterised by a high degree of adsorption deformation (swelling) compared to Al 2 O 3 . Additionally, these adsorbents form stronger covalent bonds with water molecules [ 19 , 20 , 21 , 22 , 23 , 24 ]. In this case, diffusional and chemical “traps” have higher values in comparison with the values of traps during the adsorption–desorption of water vapor on the Al 2 O 3 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Shungite is also known as the most promising nanosorbent manufactured from ore which include carbon nanostructures and turbostratic carbon with different types of minerals such as quartz, pyrite, chlorite, and sericite. 17,18 The types of the shungite carbon are comprised of amorphous carbon, ordered graphite, fullerene, graphene layers, and glassy carbon. 19 Literature survey shows that shungite has excellent adsorption properties toward various organic compounds such as oleic acid, water-soluble resins, and amyl alcohol, and heavy metals such as Zn, Cd, Pb, Mn, Cr, Cu, and Ni in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%